Classical Guidance Services in Reducing Gadget Addiction in Grade VII Students of SMPN 1 Balongan - Astri Racmawati; Evi Aeni Rufaedah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Gadgets are sophisticated devices equipped with various applications that can provide a variety of news media, social networks, hobbies, and even entertainment. This means that gadgets already provide everything needed and required by all groups, especially students. The development of technology (gadgets) is currently experiencing rapid progress, marked by advances in the fields of information and technology. The purpose of this study was to determine the effectiveness of classical guidance services in reducing gadget addiction among students at SMPN 1 Balongan. The subjects were seventh-grade students at SMPN 1 Balongan, using a case study method. The results showed several factors contributing to students' gadget addiction, including loneliness, environmental factors, and poor parental role models. However, the researchers observed that students were able to reduce their gadget addiction after receiving classical guidance services.